Evaluating the impact of individual and country-level institutional factors on subjective well-being among entrepreneurs - Albanë Gashi; Besnik A. Krasniqi; Veland Ramadani; Gentrit Berisha (Journal of Innovation & Knowledge (JIK), 2024)
This study examines entrepreneurs' subjective well-being (SWB) in the form of life satisfaction. It presents a multilevel analysis approach explaining the relationship between individual-level variables (demographics and developed personal characteristics), country-level institutional variables (political stability, corruption perception index, paying tax regulations, and business freedom), and entrepreneurs' SWB. The multilevel mixed-effects logistic regression analysis is used to test the econometric model with data from the Life in Transition Survey III for 34 countries. Findings show that both individual and governing factors play a significant role in shaping entrepreneurs' SWB. The individual-level variables such as job satisfaction, financial situation, generalized trust, optimism, and social standing are the most critical factors driving self-employed life satisfaction. On the institutional level, business freedom and political stability are the most instrumental, followed by the corruption perception index and paying tax regulatory. Overall, this research enhances comprehension regarding SWB within the entrepreneurship domain, yielding significant implications for entrepreneurship theory and practice within the well-being framework, along with providing pertinent recommendations for policymakers.
Keywords: 650; Entrepreneurship; Individual-level variables; Life satisfaction; Self-employed; Subjective well-being